Carbon-Based Electrocatalysts Derived From Biomass for Oxygen Reduction Reaction: A Minireview - Wang, Mi; Wang, Shiyu; Yang, Haoqi; Ku, Wen; Yang, Shuchen; Liu, Zhenning; Lu, Guolong (Frontiers in Chemistry, 2020)
Oxygen reduction reaction (ORR) electrocatalysts derived from biomass have become one of the research focuses in hetero-catalysis due to their low cost, high performance and reproducibility properties. Related researches are of great significance for the development of next-generation fuel cells and metal-air batteries. This review focuses on the recent progresses in the field of biomass derived ORR catalysts. We summarizes various biomass-derived catalysts prepared methods and their performance in alkaline, neutral and acidic media. At present, the biomass precursors are mainly from plant-based materials and few from animal-based materials, such as corncob, chitosan, corn stovers, dandelion seed, tribute, chrysanthemum, flowers, malachium, aquaticum, microalgae, lotus root, shaddock peel, coconut shells, mulberry leaves, sewage sludge, bagasse, enoki mushroom, sewage sludge, corn starch, starch, as well as waste leather, egg and bacteria. And the specific surface areas of biomass-derived catalysts are mainly distributed in the range of 500-2100 m2g−1, because the activation process can prepare amount of meso- and micro-porous. Through the analysis, we think that biomass-derived catalysts are more suitably applied in alkaline environment. This discovery can give us an important enlightenment to practical application in the future.